Legal destructive entrepreneurship in the modern economy - Ziętarski, Jarosław (Ekonomia i Prawo. Economics and Law, 2018)
Motivation: Usually examples of activities that have a positive impact on the economy of the state are cited. Destructive entrepreneurship refers to activities that have negative impact on the economy. This phenomenon is relatively new in the literature and does not yet have a precise definition. Aim: The aim of this article is to attempt a definition of the phenomenon of legal destructive entrepreneurship. The author also analysed the characteristics of legal entrepreneurial behaviour that have a negative impact on the economy of the state. Results: Based on the different definitions the author proposes to adopt a definition on the basis of which a division into legal and illegal entrepreneurship as well as productive, unproductive and destructive entrepreneurship was made. Author provides comparative analysis of different types of legal destructive entrepreneurship and gives examples of its manifestation under modern economy.